UPAYA MERAIH JABATAN PEMIMPIN PERSPEKTIF HADIS AHKAM - Toha Andiko (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
In public leadership, Islamic history records that succession occurred after the death of the Holy Prophet was carried out with various variants. The traditions of the Prophet who spoke about leadership, the majority discussed the ethical principles of the position of leader. Only a few hadiths discuss the law of trying to reach a leadership position, and that is generally understood as a prohibition. In fact, in the Indonesian context, for example, there is no public leadership that can be achieved without effort. This paper explains that the effort to reach a leadership position is basically not prohibited. The prohibition on asking for office in the traditions of the Prophet was actually addressed to people who were greedy and incompetent. As for someone who has more ability than most of his community, whether intellectual, managerial or other strengths that can support his leadership in the future, then the law is permissible.